Fermion dark matter in the vector scotogenic model: a survey of signatures - Paulo Areyuna C; Jilberto Zamora-Saa; Alfonso R. Zerwekh (European Physical Journal C: Particles and Fields)
Abstract In this work, we have studied the vector scotogenic model in the context of the dark matter problem. Due to unitarity considerations, we have focused on the scenario with fermion dark matter, finding out that co-annihilations play a fundamental role in achieving dark matter relic abundance. Moreover, the coannihilation effects allow to separate the parameter space into two regions with different phenomenology. In addition, we have studied the detection prospects of these regions separately, focusing on signatures that can appear in lepton flavor violating decays, indirect and direct searches, and the production of these new particles at collider facilities.